Development and Characterization of 15 Polymorphic Dinucleotide Microsatellite Markers for Tule Elk Using HiSeq3000. (16th September 2016) - Sacks, Benjamin N.; Lounsberry, Zachary T.; Kalani, Tatyana; Meredith, Erin P.; Langner, Cristen
Abstract: The tule elk ( Cervus elaphus nannodes ) experienced a severe bottleneck in the 1800s, resulting in low genetic diversity. There is a need for high-resolution genetic assays that can be used to differentiate individual elk, including close relatives, with high confidence. An efficient assay requires multiple markers both polymorphic and that can be amplified in concert with other markers in multiplex reactions. To develop such markers, we employed 150-bp paired-end whole genome shotgun sequencing on an Illumina HiSeq3000 platform to discover dinucleotide microsatellite markers. After preliminary screening of these markers, we selected and screened 15 candidate loci and 5 existing tetra nucleotide markers in 56 tule elk. We combined these markers in 2 multiplex reactions and report primer concentrations and PCR conditions enabling their efficient amplification.